Burying nutrition myths and activating choices for our children's development: Summary Paper from the International Conference on Sustainable Food Security For All By 2020 - Haddad, Lawrence J. (International Food Policy Research Institute, 2001)
The author discusses "6 myths that have made us complacent about malnutiriton and stifle our collective appetite for action... He looks at the numbers of malnourished infants, the relationship between nutrition and economic growth and alleviation of poverty, and the relationship between income growth and child malnutrition. He asks the question of why developing countries cannot do more to reduce hunger, why our collective knowledge does not lead to a solution to malnutrition and how much money is actually needed to eradicate hunger. In all six cases, he describes a myth that stands in the way of activating children's development. (From author's introduction)"